Educação Física no ensino médio noturno: a unidade didática esporte a partir da perspectiva dos estudantes - Rocha, Francisco Lucas Silva (2022)
The purpose of this paper was the proposition of a Sports learning unit for night shift high school Physical Education lessons. During the development of this research, it was possible to know the public who study during the night shifts and their particularities. Regarding theory, a state of the art study was conducted, focusing on legal aspects of both Physical Education in school, and night shift specificities. Methodologically, the qualitative approach was selected. The research samples are 18 freshman, sophomore, and senior year night shift high school students from a state school of Ceará, located in Cascavel-Ce. The instruments used for collecting data were: Google Forms open questionnaires, in which the interviewee is free to use their own communication language, since physical contact was deemed undoable because of COVID-19. Theme analysis was used for discussing the results. Upon analyzing the questionnaires’ answers, some data was highlighted, such as the age group of students ranging from 15 to 29 years old; 55,6% of the interviewees work before going to school. It’s important to note that a student diagnosis was conducted, which extends also to the object of Sports knowledge. After the analyses of the students’ answers, the proposal was to build a didactic unit, subsidized by Paulo Freire’s words, and his relevant contributions. It was perceived that participative planning displayed itself as a viable methodology for the night shift highschool teaching, since it takes into consideration the reality of this public and for contextualizing the ways teaching. It was verified that bringing these working students together in the pedagogical construction is a differential factor. They, along with their teachers, will be able to discover their potential and become more. It was possible to state that participative planning has shown itself viable and palpable as a real possibility so that these students can not only see night shift high school teaching as their evening moral obligation, but also as a combustion to drive forward their life and professional goals.